2018
DOI: 10.5115/acb.2018.51.4.225
|View full text |Cite
|
Sign up to set email alerts
|

A cadaveric study on variations in branching pattern of external carotid artery

Abstract: Variations in the vascular anatomy of the carotid triangle have been reported in current scientific literature. The carotid arteries, being the major feeding arteries of the head and neck deserve special importance and protection from iatrogenic injury during radiological evaluations and surgical interventions. The present study was carried out over a period of 4 years from 2012–2016 to assess the variant anatomy of external carotid artery. The external carotid artery and its branches were dissected bilaterall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 30 publications
(34 reference statements)
3
28
1
Order By: Relevance
“…The distribution of branching patterns of carotid arteries in this study is quite different from other studies [Table 6]. [571011152728] The percentage of facial arteries that arose in common trunk with lingual arteries (linguofacial trunk) was more frequently found (29.2% vs. 0%–20%). The branching patterns of the occipital artery had the same distribution as the previous study.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…The distribution of branching patterns of carotid arteries in this study is quite different from other studies [Table 6]. [571011152728] The percentage of facial arteries that arose in common trunk with lingual arteries (linguofacial trunk) was more frequently found (29.2% vs. 0%–20%). The branching patterns of the occipital artery had the same distribution as the previous study.…”
Section: Discussioncontrasting
confidence: 96%
“…Interestingly, even in the era of modern imaging techniques, most of the studies about the carotid bifurcation and the branching patterns were still performed in cadaveric specimens. [5678910111213141516] We believe that computed tomographic angiogram (CTA) of carotid can provide excellent visualization of anatomical variations and can be applied in clinical practice comparable to or even better than cadaveric data. Some studies used CTA or magnetic resonance angiography (MRA) of carotid as a method to determine the level of the carotid bifurcation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the CCA usually bifurcates at the level of the C3 level. Recently, a higher level of origin was noted in 20 of 80 cadavers (25%) (Devadas et al 2018). They concluded that the higher level of the carotid bifurcation exhibited a great degree of anatomical variability.…”
Section: C2mentioning
confidence: 98%
“…After these branches, the ECA branches off into the posterior auricular artery (PAA), maxillary artery (MA), and superfi-cial temporal artery. Some common trunks, such as thyrolingual, linguofacial, thyrolinguofacial, occipitoascending pharyngeal, and occipitoauricular trunks, were also identified (Zümre et al 2005;Tanaka et al 2010;Devadas et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The linguofacial trunk is a well-known possibility of variation in which the LA and FA could emerge from the ECA [12]. The incidence of the linguofacial trunk has been reported being 7% [2], 7.5% [26], 10% [5], 18% [20], 20% [7,40], or 21% [24].…”
Section: The Linguofacial Trunkmentioning
confidence: 99%